Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Help with function fi

  1. Nov 12, 2012 #1
    Hi,

    I need help in the following demonstration:

    If [itex](m,n)=d[/itex] then [itex]\Phi(mn)=\frac{d}{\Phi(d)}\Phi(m)\Phi(n) [/itex]

    Thank you very much for your support! :D
     
  2. jcsd
  3. Nov 12, 2012 #2
    Ok, so first begin by letting m= p[itex]^{κ_{1}}_{1}[/itex]...p[itex]^{κ_{r}}_{r}[/itex] and n=p[itex]^{β_{1}}_{1}[/itex]...p[itex]^{β_{r}}_{r}[/itex], where κ[itex]_{i}[/itex],β[itex]_{i}[/itex]≥ 0 [itex]\forall[/itex]i. Then (m,n)= p[itex]^{δ_{1}}_{1}[/itex]...p[itex]^{δ_{r}}_{r}[/itex], where δ[itex]_{i}[/itex] = min{κ[itex]_{i}[/itex],β[itex]_{i}[/itex]}. Then use the fact that [itex]\Phi[/itex](w) = w[itex]∏^{i=1}_{r}[/itex] (1-1/p[itex]_{i}[/itex]), given that w = p[itex]^{κ_{1}}_{1}[/itex]...p[itex]^{κ_{r}}_{r}[/itex] to rewrite [itex]\Phi[/itex](mn). At this point, it isn't too difficult to come up with the desired result. If you rewrite the right side of what you are trying to prove, it helps to at least see where you should go next.

    Also, as a side note, [itex]\Phi[/itex] is spelled 'phi' :tongue:
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook